Métodos geoelétricos aplicados ao diagnóstico ambiental subsuperficial do Cemitério Municipal de Rio Claro, SP - Xavier, Fernanda Vieira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Cemetery slurry is an effluent generated from the decomposition of organic bodies. In cemetery areas, the major cause of subsurface pollution is its percolation, which significantly alters the soil features limiting its functional performance. Particularly in Brazil, due to a historical lack of consequent planning, cemeteries are mostly located fully integrated into the urban fabric, representing a public health problem. The slurry can cause contamination of soil and groundwater due to the presence of nitrogen compounds, heavy metals, viruses and bacteria, and others risks to human health. In the literature the presence of contaminants in the geological environment often resulted in low resistivity values when compared to not affected areas. This research aimed to qualitatively investigate the subsurface of the cemetery in Rio Claro, São Paulo, to identify any changes, correlated with contaminants by inter-relationship between the geophysical responses and analytical results on monitoring wells in order to subsidize indicative assumptions of geophysical anomalies. This paper presents and discusses the results of application of Electromagnetic profiling (using Geonics EM34) and electrical resistivity method, using the Vertical Electrical Sounding techniques (Schlumberger) and 2D Electrical profiling / dipole - dipole and Gradiente. Two geoelectric main layers were defined, related to the local geology - Rio Claro Formation and Corumbataí Formation. Test results allowed the definition of three major classes of resistivity ranges giving rise to interpretations of possible contaminated areas. They are: (i) low resistivity values as potentially impacted areas; (ii) intermediate resistivity values, as transition areas, with possible influence of the contaminant; (iii) and high resistivity values, such as areas without physical changes in the environment represented by natural geological conditions. Such interpretations are discussed and ...

Necrochorume é um efluente gerado a partir da decomposição de corpos. Em áreas de cemitério, a principal causa de poluição subsuperficial é a sua percolação, que altera significativamente o solo impedindo-o de realizar suas funções naturais. Particularmente no Brasil, pela falta de planejamento consequente do histórico cultural, os cemitérios se localizam totalmente integrados à malha urbana, representando um problema de saúde pública. O necrochorume pode causar contaminação dos solos e águas subterrâneas, devido à presença de elementos, tais como compostos nitrogenados, metais pesados, vírus e bactérias, com riscos inerentes à saúde humana. Na bibliografia, essa presença de contaminantes no ambiente geológico muitas vezes resultou em baixos valores de resistividade quando comparados a uma área que não impactada. A presente pesquisa objetivou investigar qualitativamente o meio físico subsuperficial do cemitério, para reconhecer eventuais alterações, correlacionáveis às presenças de contaminantes (necrochorume), através da inter-relação entre as respostas geofísicas e os resultados analíticos dos poços de monitoramento e assim, subsidiar pressupostos indicativos de anomalias geofísicas no cemitério municipal de Rio Claro, São Paulo. Portanto, o presente trabalho apresenta e discute os resultados de aplicação de Imageamento Eletromagnético (usando Geonics EM34) e método de resistividade elétrica, utilizando as técnicas de Sondagem Elétrica Vertical, (Schlumberger) e Imageamento Elétrico 2D/dipolo - dipolo e Gradiente. Foram definidos dois estratos geoelétricos principais, referentes à geologia local - Formação Rio Claro e Formação Corumbataí e os resultados dos ensaios permitiram a definição de três classes principais de faixas de resistividades que deram margem às interpretações sobre possíveis áreas contaminadas. São elas: baixos valores de resistividade como áreas...
Keywords: Cemitério Municipal São João Batista (Rio Claro, SP); Environmental geography; Geografia ambiental; Cemiterios; Poluição; Geofisica